The Impact of Covid-19 Pandemic to the Formation of Students Skill Dimension in Elementary School - stefanus divan; Gervasius Adam; Fabianus Hadiman Bosco (Jurnal Elementaria Edukasia, 2023)
This research intends to elucidate the effect of Covid-19 pandemic in establishing student’s skill dimension and the effort of teacher in forming student’s skill dimension at SDI Lenang Neros. This study uses qualitative approach and case study method. The subjects of the research are teachers and students. Data collection technique used an interview and document study. This research is motivated that by throughout pandemic the teachers were not yet forming the skill dimension of students. The result of this research pointed out that Covid-19 pandemic had an impact on the formation of student skill dimensions at SDI Lenang Neros. The impact of Covid-19 pandemic on the formation of student skill dimensions namely the low ability of writing, reading, drawing, dancing and the ability of measuring. During pandemic the effort of teacher in the formation of student psychomotor not yet maximized. Teacher had not used the platform online learning such Zoom, YouTube, learning video and WA to support the formation of student skill dimensions. The presented subject was only in the form of assignments and theory without practicum activity. Grounded on research findings could be concluded that Covid-19 pandemic had an impact on students’ skill dimension such lacking of motor activity obtained by the students.